Digital Media Empowering Gender Equality and Education Goals (Trinity Journal of Management, IT & Media (TJMITM), 2020)
Digital Media in today’s era plays a crucial role in empowering and setting agendas for their prompt fulfillment in the society. Consequently, it can be a boosting factor for the Sustainable Development Goals (SDGs). All the issues concerning social and economic development can be gratified by dominant portrayal through Digital Media. This research paper is the consummation of the substantial justification of Digital Media actions through pivotal testimony. Research studies the two basic goals of SDGs in-depth that are Gender Equality and Education. Study explores through the correlation results channelizing the linkage between Digital Media and SDGs by the methods of surveys, questionnaires and experiments. The Internet and its access can transform society in varied ways but governments of various states are limiting the use of it. It can increase the morale of people regarding gender equality and education; if they are injected with right wisdom instead of unnecessary abundant information. It will ultimately pour contentment to the sustainable development goals of the UN. There are numerous applications and ways of integrating the Digital media and SDGs. Study realizes the importance of belongingness among the social media users. There is a great need for a sense of attachment which requires locally created content and its dissemination through locally accessible social media platforms. Hence, it is paramount to penetrate the aspects which might influence the use of digital media like, social, economical, political factors etc. Just the awareness of the facts about gender equality and education alone cannot discharge the goals; a considerable action inactive message needs to be disposed to the society. Using digital technology a virtual space can be created, where society must not only be informed but also be engaged at large scale.
Keywords: Digital Media; SDGs; Gender Equality; Education